2019
DOI: 10.4014/jmb.1905.05016
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Butyrate Production, Ruminal Fermentation and Microbial Population through Supplementation with Clostridium saccharobutylicum

Abstract: Butyrate is known to play a significant role in energy metabolism and regulating genomic activities that influence rumen nutrition utilization and function. Thus, this study investigated the effects of an isolated butyrate-producing bacteria, Clostridium saccharobutylicum, in rumen butyrate production, fermentation parameters and microbial population in Holstein-Friesian cow. An isolated butyrate-producing bacterium from the ruminal fluid of a Holstein-Friesian cow was identified and characterized as Clostridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 62 publications
(70 reference statements)
2
13
0
Order By: Relevance
“…However, in contrast to our findings, most of those studies observed consistent decreases in the N-NH 3 concentration. Regarding ruminal fermentation, the decrease in the molar proportion of butyrate may be the only deleterious effect of the incorporation of high proportions (80%) of DOP in the diet since this fatty acid constitutes one of the greatest energy resources for stimulation of epithelial cell proliferation in ruminants [ 27 ], which contributes directly to improving the efficiency of feed utilisation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our findings, most of those studies observed consistent decreases in the N-NH 3 concentration. Regarding ruminal fermentation, the decrease in the molar proportion of butyrate may be the only deleterious effect of the incorporation of high proportions (80%) of DOP in the diet since this fatty acid constitutes one of the greatest energy resources for stimulation of epithelial cell proliferation in ruminants [ 27 ], which contributes directly to improving the efficiency of feed utilisation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira, a member of another potential pathogen Spirochete, can cause leptospirosis that principally infects domestic and wild mammals and is a secondary infection of humans (Gupta et al, 2013). Many species in genus Clostridium were thought to be butyric acid producer, and can stabilize ruminal pH by consume lactate (Miguel et al, 2019;Cai et al, 2021). However, Clostridium also includes several significant pathogens which can cause Clostridial abomasitis and enteritis in all species of domestic ruminants (Simpson et al, 2018), and can cause the causative agents of botulism and tetanus in human (Cruz-Morales et al, 2019).…”
Section: Do Microbes Show Convergence Inmentioning
confidence: 99%
“…The declined ammonia concentrations in those studies might be attributed to a higher efficiency in consuming ammonia for microbial protein synthesis in the rumen. Butyrate plays a prominent role as a major energy source for epithelial cells [ 59 ] and affects rumen nutrition utilisation and function [ 60 ]. In the present study, thymol at doses of 100 mg/L and 200 mg/L tended to increase butyrate concentration while a dramatical decrease was observed with 400 mg/L of thymol supplementation.…”
Section: Discussionmentioning
confidence: 99%